# algebra

posted by .

(4)/(x+2) - (4)/(x)
__________________ = 1
2

• algebra -

(4/(x + 2) - 4/x)/2 = 1

rewrite as
(4/(x + 2) - 4/x) * 1/2 = 1
4/(2(x + 2)) - 4/2x = 1
4/(2x + 4) - 4/2x = 1
LCD 2x(2x + 4)
(8x - 4(2x + 4))/(2x(2x + 4)) = 1
multiply both sides by 2x(2x + 4)
8x - 4(2x + 4) = 2x(2x + 4)
8x - 8x -16 = 4x^2 + 8x
-16 = 4x^2 + 8x
4x^2 + 8x + 16 = 0
4(x^2 + 2x + 4) = 0
divide both sides by 4
x^2 + 2x + 4 = 0

Solve this by Quadratic formula or completing the square

I leave the rest to you to solve

## Similar Questions

1. ### algebra attn Reiny

Thanks for your help with the solving of the three equations! Yes, it was a typo. I just finished solving it a long way, solving for the 1st 2 equations then the 2nd and 3rd and plugging in variables...etc. etc. Your way gave the same …

3. ### algebra

ok, Thanks for the help on that last one but can you help me with these: solving equations with the variable on each side. 1.) 6+2(3j-2)=4(1+j) 2.) 9(4b-1)=2(9b+3) please help
4. ### Algebra

Need help solving the system of inequalities and equations graphically for this problem. Please help! 6y=9(x-6) 3(2y+5x)=-6
5. ### Algebra SOLVING LINEAR EQUATIONS AND INEQUALITIES

Please help Im am Grade 5 and my teacher is letting me do this. 1. Solve the solution by using elimination and substitution 3/x - 2/y = 14 6/x + 3/y = 7 2. Solve by eliminating x (this is solving 3 linear equations) then substitute …
6. ### Algebra I DONT KNOW HOW TO DO 3 VARIABLES

Solving Linear Equations and Inequalities Solve by eliminating x (this is solving 3 linear equations) then substitute to the other two equation x + y + 5z =2 (1) 4x - 3y + 5z =3 (2) 3x - 2y + 5z=1 (3) my teacher gave me the answer …
7. ### Algebra

Solving Linear Equations and Inequalities Solve by eliminating x (this is solving 3 linear equations) then substitute to the other two equation x + y + 5z =2 (1) 4x - 3y + 5z =3 (2) 3x - 2y + 5z=1 (3) my teacher gave me the answer …
8. ### geometry

You are given that 2 2 2 2 ac c  bc  with c ≠ 0. Show that 4b = 4c − a by filling in the blanks. a. 2 2 2 2 ac c  bc  a. Given b. 4c2 = 4bc + ac b. __________________ and __________________ …